Behavioral intention to use distance teaching in the pandemic era - Tseng, Chih-Hung; Wang, Ching-Tang; Hsu, Chin-Hsien; Liu, Jing-Wei (Frontiers in Psychology, 2022)
This research conducted an empirical study on the impact of the behavioral intention of using distance teaching in the post-epidemic era. Via intentional sampling, 390 questionnaires in total were distributed, 360 questionnaires were returned with a recovery rate of 92%, and 329 valid questionnaires were returned with a recovery rate of 91%. For data analysis, descriptive statistics were adopted to analyze the distribution of background variables for teachers in colleges and universities, high schools and vocational schools, and junior high and elementary schools. The structural equation model was used to verify the impact between the Technology Acceptance Model (perceived usefulness, perceived ease of use, attitude of use, and intention to use), Information System Success Model (information quality, system quality, and service quality), and Diffusion of Innovations Theory (related advantages, compatibility, trialability, and observability). As found in the research results, for teachers of distance teaching in colleges and universities, high schools and vocational schools, and junior high and elementary schools, information quality has a significant impact on perceived usefulness, information quality has no significant impact on perceived ease of use, system quality has no significant impact on perceived usefulness, system quality has no significant impact on perceived ease of use, service quality has no significant impact on perceived usefulness, service quality has no significant impact on perceived ease of use, perceived ease of use has a significant impact on perceived usefulness, perceived usefulness has a significant impact on attitude of use, perceived ease of use has no significant impact on attitude of use, related advantages have no significant impact on attitude of use, compatibility has no significant impact on attitude of use, trialability has a significant impact on attitude of use, observability has no significant impact on attitude of use, and attitude of use has a significant impact on intention to use. Practical suggestions and research recommendations were proposed by this study based on the research results, and they are expected to be used by teachers in colleges and universities, high schools and vocational schools, junior high schools, and elementary schools for reference in distance teaching.